Singing Method Application in Improving Memorizing of Obligatory Characteristics of Allah to Madrasah Diniyah Students - Muhammad Toharudin; yusron fadili; Siti Roudhotul Jannah; Subandi Subandi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2023)
Music or songs are the result of a combination of beautiful lyrics and melodies, which is why everyone likes them, both the community of young children and adults. Therefore, the use of music or songs is also used in the teaching and learning process to change learning which was originally boring to be fun. This research aims to find out how educators improve the memorization of Allah's obligatory attributes using the singing method at Madrsah Diniyah Takmiliyah Darul Huda Lubuk Harjo, South Sumatra. In collecting data, researchers used observation, documentation, and interview techniques. The results of the study show that the efforts made by educators in developing rote memorization of Allah's obligatory attributes with the singing method are carried out when the subject teacher is about to take midterm exam scores. Subject teachers teach songs that will be used in memorizing the obligatory attributes of Allah and then imitated by students. The results show that the singing method can improve students' memorization